Lichtenstein Procedure for Inguinal Hernia Repair With or Without Fixation of Mesh - ullah, Misbah; Arooj, Sana; Ahmad, Munir; ullah, Zahid; Aizaz Kamal, Muhammad (ADVANCES IN BASIC MEDICAL SCIENCES, 2022)
Objective: To compare the safety and efficacy of the Lichtenstein repair with and without mesh fixation for inguinal hernia. Methodology: This randomized controlled trial was conducted at the Department of Surgery, Khyber Teaching Hospital, Peshawar from 1st March 2020 to 30th September 2021. A total of 234 patients diagnosed as cases of inguinal hernia were included in the study and randomly allocated to groups with mesh fixation (group A) or without mesh fixation (group B) by the flip coin method. The visual analogue sale was used for the assessment of pain after surgery. All the data were analyzed by using SPSS software version 26. Results: All the subjects included in the study were male in both groups. There was a significant increase in the time of operation in group A (38.18±4.5 minutes) compared to group B (33.85±5.99 minutes) with a p-value of <0.001. There was no significant difference in the hospital stay in both groups. The Visual Analogue Scale for pain showed a significant reduction of pain in group B (2.40±0.810) as compared to group A (3.66±1.123) p-value <0.001. There was no recurrence noted in either group up to three months follow up. Conclusion: It is concluded that the Lichtenstein procedure with no mesh fixation technique for inguinal hernia repair is safe, less time-consuming, and less postoperative pain.